1980
DOI: 10.1246/bcsj.53.169
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Nazarov Reaction. A New Synthetic Approach to 2,3-Disubstituted 2-Cyclopentenones

Abstract: Acid-catalyzed reaction of β,β′-disubstituted cross conjugated dienones or the corresponding ethylene acetals gives mainly 2,3-disubstituted 2-cyclopentenones in stead of the simple Nazarov cyclization products, 3,4-disubstituted 2-cyclopentenones. This transformation is explained in terms of electrocyclic ring-closure, addition of hydroxylic solvent(s), tautomerization of the resulting 2-hydroxycyclopentanone intermediates, followed by solvolysis and isomerization. Based on this working hypothesis a new route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Trapping with heteroatomic solvents such as methanol, acetic acid, trifluoroacetic acid, or formic acid has been observed in photo-Nazarov cyclizations, 17 and in cyclizations promoted by protic acids. 18 Intramolecular oxygen interruption is also possible during Lewis acid-promoted cyclization, 19 as well as intermolecular trapping with azides, 20 halides 21 or amines. 12b, 22 In addition to hydride shift and methyl shift, a vinyl migration following electrocyclization of a linear dienyl ketone was also reported by Denmark and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…Trapping with heteroatomic solvents such as methanol, acetic acid, trifluoroacetic acid, or formic acid has been observed in photo-Nazarov cyclizations, 17 and in cyclizations promoted by protic acids. 18 Intramolecular oxygen interruption is also possible during Lewis acid-promoted cyclization, 19 as well as intermolecular trapping with azides, 20 halides 21 or amines. 12b, 22 In addition to hydride shift and methyl shift, a vinyl migration following electrocyclization of a linear dienyl ketone was also reported by Denmark and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage, Piancatelli et al synthesized cyclopentenones from furans, where the reaction was catalyzed by a homogeneous strong acid in an acetone/water system. 5 Synthetic methods using other starting materials such as alkynes, alkenes, carbon monoxide, 3,6 dienones, 7 1,3-dicarbonyl compounds, 8 isoprene, 9 mesyltriflone, 10 diazo ketones, 11 alkynones, 12 and HDN (2,5-hexanedione) 13,14 were also developed. It is worth mentioning that HDN can be obtained by the hydrolysis of a HMF-derived product, 2,5-dimethylfuran (DMF).…”
Section: Introductionmentioning
confidence: 99%
“…The Nazarov reaction is an acid-catalyzed cyclization of divinyl ketones to 2-cyclopentenones . The reaction has been used in construction of many complex, natural, and biologically important target molecules and their synthetic intermediates possessing the cyclopentenone moiety, such as jasmonoids and prostanoids . The Nazarov reaction involves a conrotatory 4π electrocyclization of the pentadienyl cation, and it is therefore considered as a pericyclic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The Nazarov reaction produces normally 3,4-disubstituted 2-cyclopentenones 2 from β,β‘-disubstituted cross conjugated divinyl ketones 1 (Scheme ). However, Hirano et al have reported about the abnormal Nazarov reaction, in which the main product is a 2,3-disubstituted 2-cyclopentenone 3 . , They postulated that this unexpected product is formed by the addition of a hydroxylic solvent, such as water or carboxylic acid, to the oxyallyl cation 5 after the electrocyclic ring closure of the protonated divinyl ketone 4 (Scheme ). This would give rise to the hydroxy- or acyloxycyclopentenone intermediate 6 , which isomerises to 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation